A comparative study of narrow-band ultraviolet B alone versus with low dose simvastatin in the treatment of vitiligo: impact on chemokine C-X-C motif ligand 10 and chemokine C–C motif ligand 8 - Shaimaa I. Omar; Adel El Shafey; Nermeen Eldabah; Asmaa Hafez (Journal of the Egyptian Women’s Dermatologic Society)
Background Our knowledge of the pathophysiology of vitiligo has advanced significantly. However, there are still some unclear aspects. Chemokine C-X-C motif ligand 10 (CXCL10) is a biomarker of vitiligo activity and chemokine C–C motif ligand 8 (CCL8) is a chemokine that has been studied recently in vitiligo pathogenesis. Objective The primary objective was to compare the efficacy and safety of adding low-dose simvastatin to narrowband ultraviolet B (NB-UVB) versus NB-UVB monotherapy for vitiligo treatment including the effect on CXCL10 and CCL8. The secondary objective was to look for any potential links between CCL8 and vitiligo. Patients and methods In this interventional comparative study 50 vitiligo patients were enlisted and randomly split into two groups: the treatment group received NB-UVB plus simvastatin, while the control group received NB-UVB alone for 3 months. Enzyme-linked immunosorbent assay kits were used to test the serum levels of CXCL10 and CCL8, and the vitiligo area scoring index (VASI) score was computed both before and after therapy. Results Following treatment, the median values of the VASI score reduction were considerably higher (P=0.037) in the treatment group (1.50) in comparison with controls (0.52). In addition, the median serum levels of CXCL10 and CCL8 were significantly lower (P=0.003 and 0.030, respectively) in the treatment group (132.6 and 110.8 ng/l, respectively) than in the control group (155 and 122.8 ng/l, respectively). There were no side effects noted. CCL8 and CXCL10 serum levels had a positive correlation. Conclusion The outcomes of the therapy point to the potential for simvastatin to work in conjunction with NB-UVB to treat vitiligo. Current findings also suggest that CCL8 may play a role in the pathogenesis of vitiligo. In this study, CXCL10 is not correlated with disease severity.